A Signature of Passivity? An Explorative Study of the N3 Event- Related Potential Component in Passive Oddball Tasks - Kotchoubey, Boris; Pavlov, Yuri G. (Frontiers in Neuroscience, 2019)
Many passive oddball experiments show a sharp negative deflection N3 after P3b, peaking between 400 and 500 ms, but this wave has never been analyzed properly. We conducted five passive oddball experiments, in which the number of deviants (i.e., one or two), their alleged meaning and their distinctiveness varied. Mastoid- or common-referenced waveforms showed a fronto-central N3 in all experiments. The data were CSD (Current Source Density) transformed and underwent a Principal Component Analysis (PCA). The PCA revealed N3 containing two subcomponents with very stable peak latencies of about 415 and 455 ms, respectively. Both topography of the subcomponents and their variation with experimental conditions were very similar, indicating a midfrontal sink and a posterior temporal source. Positive components P3a and P3b were also analyzed, replicating the previously known effects. We discuss the similarities and differences between the passive N3 and other components including the MMN, N1, late positive Slow Wave, and reorienting negativity. We also make general hypotheses about a possible functional meaning of N3; on this basis, specific hypotheses are formulated and further experiments are suggested to test these hypotheses.